Adherence to antihypertensive drug treatment in patients with apparently treatment-resistant hypertension in the INSPiRED pilot study. (4th May 2019) - Wunder, Cora; Persu, Alexandre; Lengelé, Jean-Philippe; MG Georges, Coralie; Renkin, Jean; Pasquet, Agnès; Carlier, Marc; Zhang, Zhen-Yu; Staessen, Jan A.; ,
Abstract: Purpose: Drug adherence may be a major problem in the therapy of hypertension and in the diagnosis of therapy resistance. Adherence can be assessed by indirect methods or by direct methods like drug detection in urine with liquid chromatography-mass spectrometric methods. Materials and methods: The current analysis included patients with apparently treatment- resistant hypertension (TRH) referred for renal denervation (RDN) and included in the the INSPiRED pilot trial (NCT 01505010). Adherence was repeatedly assessed by toxicological urine analysis over a time range of up to 17 months in a total of 18 patients. Results: In the first urine samples of 18 patients the adherence rate (percentage of number of detected vs. prescribed medical drugs) ranged from 0 to 100% with a median of 73.2%. In further urine samples collected during the following up to 17 months every individual patient exhibited considerable changes in the adherence rate, neither a constancy nor a tendency could be deduced. Conclusions: Urine analysis results exhibit variation over time and an assessment at a certain time point cannot be regarded as representative or predictor for future behavior. Therefore, it appears necessary to perform drug adherence testing repeatedly over time. Trial registration: ClinicalTrials.gov identifier: NCT01505010.